Hibridni odprti javni prostor krajinskih elementov in grajene strukture - Bence, Gordana (Urbani izziv, 2008)
The trend today in the cities in Europe and elsewhere is in combining landscape elements, built structure and different uses into a complex urban structure. Physical and program interweaving of landscape elements and built structure enables the consumers daily practice of leisure programs - relaxation, recreation and experiencing other cultural, educational and social events in the public green space. On the basis of determinate social changes and new approaches in urban planning practice, analyses of architectural and urban case studies from the point of view of integrating the landscape elements into the urban structure, the article defines the phenomen on of hybrid open public space and proposes methodical guidelines for the planning.
Keywords: bivalno okolje; javni prostor; krajina; mesta; urbana naselja; urbani prostor